STRATEGI PENGEMBANGAN KAWASAN STRATEGIS GERBANGKERTOSUSILA BERBASIS PERTUMBUHAN EKONOMI DAN PEMERATAAN PEMBANGUNAN DI JAWA TIMUR - Hurairah Haqi Ikhlasi; Sabrina Chaerani Astuti; Gildha Eka Putri; Belinda Ulfa Aulia (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
The strategic area of Gerbangkertosusila in East Java has experienced significant economic growth, yet it is accompanied by development disparities across regions. Surabaya City, as the core area, contributes the most to the Gross Regional Domestic Product (GRDP), while peripheral areas such as Bangkalan, Lamongan, and Mojokerto City lag economically and socially. This research aims to formulate a development strategy that not only promotes economic growth but also ensures equitable development. Using descriptive statistical analysis, the Williamson Index, and SWOT analysis, the study finds that the Williamson Index value for Gerbangkertosusila remained high over the past five years (average 0.8442), indicating substantial disparities. The proposed development strategy focuses on enhancing interregional connectivity, diversifying economic sectors in peripheral areas, and promoting equitable investment to achieve inclusive and sustainable growth across the metropolitan area.